O silêncio do sagrado: meninas abusadas sexualmente pela figura paterna em Goiânia - Paro, Carmen Regina (2003)
The aim of the study of the Silence of the Sacred: little girls sexually abused by the father figure in Goiânia brings the discussion about the child in the bourgeois sociability, historically considered as an incapable being where her conditions of little girl places the gender category in a relation of the man s power over the woman, converging the difference in inequality. It has the main goal of understanding if the God-Father figure that is present in the children girl, who are seen by Aldeia Juvenil Center of Study and Research, has contributed to the maintenance of the silence that is present in the sexual abuse committed by fathers against daughters. For such investigation, six cases of girls in the ages of six to eleven years old, in situation of sexual violence interfamily whose silence was broken by the revelation to an adult person who believed them were analyzed. These were defined not only by the criteria of the biological father but also by the masculine figure who plays this role. As a constitutive of this reality one has the mediation of the religious field whose supreme divinity is in God, masculine, father, from a superior hierarchy, covered of absolute potentiality, not questionable, sacred, untouchable who is going to compose the cultural ethos of our society. These attributes reinforce the masculine power and keep the abused girl in a prison through the silence.